Stability, rheological property and oil-displacement mechanism of a dispersed low-elastic microsphere system for enhanced oil recovery. Issue 14 (23rd January 2017) - Yang, Hongbin; Kang, Wanli; Wu, Hairong; Yu, Yang; Zhu, Zhou; Wang, Pengxiang; Zhang, Xiangfeng; Sarsenbekuly, Bauyrzhan
Abstract : The dispersed low-elastic microsphere system shows shear-thickening behavior because of the microstructure change and the interaction of internal forces. Abstract : A dispersed low-elastic microsphere system, consisting of low-viscoelastic microspheres and polymers, is a novel suspension system for enhanced oil recovery in heterogeneous reservoirs. In this study, experiments were performed to characterize the morphology, viscoelasticity, and swelling performance of the synthetic low-elastic microspheres. The stability and rheological property of the dispersed low-elastic microsphere system was investigated using a Turbiscan Lab Expert stability analyzer and an MCR301 rheometer. In the flow and displacement experiments, the parallel-sandpacks model and microscopic visualization models were used to study the oil-displacement effect and micromigration mechanism of the low-elastic microspheres. The experimental results showed that the storage modulus ( G ′) of the synthetic low-elastic microspheres was only 23.6 Pa and they also had a good swelling property in the simulated formation water. The parallel-sandpacks test and micromodel test indicated that the dispersed low-elastic microsphere system was a promising agent for both conformance control and improved oil recovery in heterogeneous reservoirs. Moreover, the low-elastic microspheres had good deformation and shear resistance performances. Five transport behaviors, such as deformable passing through, partition passing through, blockage, adhesion, and directly passing through, of low-elastic microspheres in a porous medium have been put forward. This study not only provides an understanding of the properties of the dispersed low-elastic microsphere system but also supplies theoretical support for the mechanism of improving oil recovery for the dispersed low-elastic microsphere system.